2011
DOI: 10.1111/j.1476-5381.2011.01505.x
|View full text |Cite
|
Sign up to set email alerts
|

Cellular pharmacokinetic mechanisms of adriamycin resistance and its modulation by 20(S)‐ginsenoside Rh2 in MCF‐7/Adr cells

Abstract: BACKGROUND AND PURPOSE Intracellular pharmacokinetics of anticancer drugs in multi‐drug resistance (MDR) cancer cells is hugely important in the evaluation and improvement of drug efficacy. By using adriamycin as a probe drug in MDR cancer cells, we developed a cellular pharmacokinetic‐pharmacodynamic (PK‐PD) model to reveal the correlation between cellular pharmacokinetic properties and drug resistance. In addition, the ability of 20(S)‐ginsenoside Rh2 (20(S)‐Rh2) to reverse MDR was further investigated. EXPE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
70
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(70 citation statements)
references
References 46 publications
0
70
0
Order By: Relevance
“…a potent noncompetitive inhibitor of P-gp [13][14][15] , indicating that there may be a potential pharmacokinetic interaction between Rh2 and the P-gp substrate of PIs. Ritonavir (RTV), one of the most commonly used HIV PIs, has been demonstrated to be a substrate and inhibitor of P-gp both in vitro and in vivo [9,10,16,17] .…”
Section: Introductionmentioning
confidence: 99%
“…a potent noncompetitive inhibitor of P-gp [13][14][15] , indicating that there may be a potential pharmacokinetic interaction between Rh2 and the P-gp substrate of PIs. Ritonavir (RTV), one of the most commonly used HIV PIs, has been demonstrated to be a substrate and inhibitor of P-gp both in vitro and in vivo [9,10,16,17] .…”
Section: Introductionmentioning
confidence: 99%
“…Although the underlying mechanism of doxorubicin resistance is not fully understood, researchers have determined several factors that influence cellular doxorubicin toxicity. It has been reported that doxorubicin can induce ROS generation in various tumor cells (8,9) and inhibition of P-glycoprotein by 20(S)-Rh2 attenuates adriamycin resistance (10).…”
Section: Introductionmentioning
confidence: 99%
“…MCF-7/A cells have been verified to overexpress P-gp compared to MCF-7/S cells and they exhibit multi-drug resistance (Zhang et al, 2012).…”
Section: Cell Culturementioning
confidence: 99%
“…The efficacy of PTX and DPT on MCF-7/S and Adriamycin-resistant MCF-7/A cells was determined by cell growth inhibition via 3-(4,5-dimethyl-2-thiazolyl)-2,5-diphenyl-2Htetrazolium bromide colorimetric assay after incubation with PTX and DPT under different concentrations. The concentration required to inhibit growth by 50% (IC50 values) were calculated from the survival curves using the Bliss method (Bliss, 1939, Zhang et al, 2012Lu et al, 2015).…”
Section: Cytotoxicity Assaymentioning
confidence: 99%
See 1 more Smart Citation